Proposal of a low cost educational mobile robot experiment: an approach based on hardware and simulation - Gonçalves, José (2017)
In this paper it is presented an educational mobile robotics experiment based on a low cost mobile robot prototype and its simulation. The chosen educational robot challenge is a classical introductory experiment, that consists in following a line with a mobile robot based on the differential kinematics. The presented experiment has as goal to introduce students to the challenges of mobile robotics, initially programming a simulated robot, building a real robot and finally testing the developed code in a real robot. The robot was simulated using SimTwo, which is a realistic simulation software that can support several types of robots. Having as base the proposed challenge, a mobile robot competition was conducted as a part of the evaluation of the curricular unit of ``Systems Based on Micro-Controllers'' of the ``Electrotechnical and Computer Engineering'' course of the Faculty of Engineering of the University of Porto.